Serological Evidence for Henipa-like and Filo-like Viruses in Trinidad Bats. (8th February 2020) - Schulz, Jonathan E; Seifert, Stephanie N; Thompson, John T; Avanzato, Victoria; Sterling, Spencer L; Yan, Lianying; Letko, Michael C; Matson, M Jeremiah; Fischer, Robert J; Tremeau-Bravard, Alexandre; Seetahal, Janine F R; Ramkissoon, Vernie; et al.
Abstract: Bat-borne zoonotic pathogens belonging to the family Paramxyoviridae, including Nipah and Hendra viruses, and the family Filoviridae, including Ebola and Marburg viruses, can cause severe disease and high mortality rates on spillover into human populations. Surveillance efforts for henipaviruses and filoviruses have been largely restricted to the Old World; however, recent studies suggest a potentially broader distribution for henipaviruses and filoviruses than previously recognized. In the current study, we screened for henipaviruses and filoviruses in New World bats collected across 4 locations in Trinidad near the coast of Venezuela. Bat tissue samples were screened using previously established reverse-transcription polymerase chain reaction assays. Serum were screened using a multiplex immunoassay to detect antibodies reactive with the envelope glycoprotein of viruses in the genus Henipavirus and the family Filoviridae. Serum samples were also screened by means of enzyme-linked immunosorbent assay for antibodies reactive with Nipah G and F glycoproteins. Of 84 serum samples, 28 were reactive with ≥1 henipavirus glycoprotein by ≥1 serological method, and 6 serum samples were reactive against ≥1 filovirus glycoproteins. These data provide evidence of potential circulation of viruses related to the henipaviruses and filoviruses in New World bats.